Αδιάκοπες στο βωμό προσφορές και δίκαιη αναγνώριση : δοκίμιο Α΄ - Σίδερης, Τάσος Α. ([χ.ό.], 1986)
Ιωάννης Σ. Αλεξάκης -- Πάνος Παπαρρηγόπουλος -- Σαράντης Γ. Κωτσαρίδης -- Γεράσιμος Γρηγόρης -- Πανταζής Α. Κοντομίχης -- Γαλάτεια Μπαλτά -- Γούλα Σμυρνιώτη -- Φανή Ρουμελιώτη-Μαργαρίτη -- Αριστείδης Κλήμης -- Σπύρος Ν. Καλούδης -- Μόσχος Κεφάλας -- Σπύρος Μεσημέρης -- Γιάννης Μ. Μαρής κ.ά.